O modelo da competência e a educação do trabalhador: uma análise à luz da ontologia marxiana - Morato, Aline Nomeriano (2005)
The objective of this work is to analyze, to the light of the ontology marxiana, the proposal of the worker’s education founded in the competence notion, starting from researcher Marise Ramos’ theoretical-critical formulation. The analysis of this problem, with base in the foundations of the perspective ontologicol-marxiana, allowed to verify that in spite of representing the perspective of the work, her critical elaboration doesn’t cross the logic of the main. Referred her approach doesn’t present a thorough critic to the current relationships between work and education, not moving forward out in the sense of pointing real possibilities to exceed of those problems of the sphere of the main. The perspective presented by the researcher indicates the extent of the politics as road for the resolution of the subjects regarding the worker’s education. When facing the phenomenon of the competence notion as ethical-political problem, Ramos starts to have the politics as end, following the same road of some educatiors that articulate education and citizenship. Articulation that, that although it intends to appear for besides the system capitalist, it doesn’t get to cross the limits imposed by him. For the perspective of the centralization ontologicol of the work, the resolution of the current problems of the sociabillity of the main – among them it is the relationship work and education – it can only be looked for in the sphere of the economy, that has a determination ontologicol (no mechanics) on the politics, through the to exceed of the contradiction between main and work, following by the own dissolution of the main.